Mechanical Properties of Nanocarbon Hybrid Films via Indentation Simulation. Issue 19 (14th March 2016) - Onodera, T.; Shintani, K.
ABSTRACT: The mechanical properties of nanocarbon hybrid films are addressed by means of indentation simulation based on molecular-dynamics. In these films, single-walled carbon nanotubes (SWCNTs) are intercalated parallel to each other between graphene sheets; the SWCNT axes are also parallel to the planes of the sheets. Thus the simulation model is quasi-two-dimensional. The load-deflection curve depends on both the number of the layers and the diameter of SWCNTs. In the range of small forces, the simulation data can be interpolated by a cubic function of the deflection, while in the range of large forces, the data can be expressed in terms of a linear function of the deflection. It is revealed that such a transition corresponds to the structural change of the hybrid film.